Graus de (in)formalidade e (im)polidez linguística em comentários de redes sociais em língua russa - João Pedro Cirino Marques (2023)
This study aims at analyzing comments made in reaction to the posts of Russian celebrities and media personalities on social media, from the perspective of the usage of personal pronouns - such as вы and ты - and other marks of (in)formality - nicknames, emojis, punctuation marks - and their relation with the manifestation of linguistic (im)politeness. Drawing from this background, and considering the scarce exploration of the linguistic aspects of the Russian language, especially in interface with the field of pragmatic studies, we sought, through qualitative research, to analyze the different degrees of (in)formality present in digital discourse, specifically the one employed in the social network Instagram. To do this, morphosyntactic and pragmatic aspects were intertwined, as present in the comments from users of the social network Instagram, followers of the profiles of three very popular public figures in Russia: singers Klava Koka, Loboda, and Sergei Shnurov. In this way, it was possible to reach relevant conclusions both about how the use of pronouns classified as formal and informal in Russian is syntactically realized, as well as other marks of (in)formality, such as the use of affectionate nicknames, and their connection with the manifestation of linguistic (im)politeness. The findings also showed that, in the analyzed posts, the fluidity between the different degrees of (in)formality is a feature of the digital environment and suggests updating and familiarity with the cyber world. In addition, as adequacy to the interlocutor's expectations is a factor that occupies the primacy in human communication in general, the variation of (in)formality fulfills important communicative functions, and, for this reason, it can be seen as a socially relevant attribute, in association with the marks of (im)politeness also found.